2015
DOI: 10.1111/ahe.12190
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Immunohistochemical Characterization of Canine Osteosarcoma Spheroid Cell Cultures

Abstract: SummarySpheroid cell culture emerges as powerful in vitro tool for experimental tumour research. In this study, we established a scaffold‐free three‐dimensional spheroid system built from canine osteosarcoma (OS) cells (D17). Spheroids (7, 14 and 19 days of cultivation) and monolayer cultures (2 and 7 days of cultivation) were evaluated and compared on light and electron microscopy. Monolayer and spheroid cultures were tested for vimentin, cytokeratin, alkaline phosphatase, osteocalcin and collagen I by means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 56 publications
3
21
0
Order By: Relevance
“…Among these, Col I is considered the most promising osteospecific marker in the literature concerning human OSA (31), and was therefore a logical choice to assess in canine OSA. Both canine OSA cell lines were indeed highly positive with antibodies to Col I, consistent with the fundamental characteristic of collagen production by this tumor histotype (41,42). Osteocalcin was detected in most but not all tumor cell lines, which is in agreement with findings from immunohistochemical assays of primary tumor tissue (40,42), and studies of human OSA (31).…”
Section: Discussionsupporting
confidence: 83%
“…Among these, Col I is considered the most promising osteospecific marker in the literature concerning human OSA (31), and was therefore a logical choice to assess in canine OSA. Both canine OSA cell lines were indeed highly positive with antibodies to Col I, consistent with the fundamental characteristic of collagen production by this tumor histotype (41,42). Osteocalcin was detected in most but not all tumor cell lines, which is in agreement with findings from immunohistochemical assays of primary tumor tissue (40,42), and studies of human OSA (31).…”
Section: Discussionsupporting
confidence: 83%
“…These data confirm that 3D culture is the most useful tool to assess the ability of tumour cells to perform VM, providing a more similar physiological environment, enhancing spheroid formation . This is the first evidence for the establishment of a scaffold‐free spheroid system in canine OSA with the ability to mimic the architecture of the in vivo tumour . In non‐adherent in vitro conditions, it has been already showed that D17 cells assume stem cell characteristics which are absent in monolayer culture, also increasing collagen I and osteocalcin expression with respect to D17 monolayer .…”
Section: Discussionsupporting
confidence: 74%
“…Significant differences between treated and untreated control cells are shown by asterisks (*P < .05, **P < .01) evidence for the establishment of a scaffold-free spheroid system in canine OSA with the ability to mimic the architecture of the in vivo tumour. 47 In non-adherent in vitro conditions, it has been already showed that D17 cells assume stem cell characteristics which are absent in monolayer culture, also increasing collagen I and osteocalcin expression with respect to D17 monolayer. 31 Because tumour cell spheroids are generally less sensitive to drugs when compared to cells treated in monolayer culture, investigations on the molecular mechanisms of 17-AAG activity in canine OSA 3D cultures could offer new opportunities for the development of therapeutic strategies based on the synergy between VM-blocking and anti-angiogenic properties of Hsp90 inhibition, considering that its anti-tumour activity on OSA cells has been previously established.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the method used by Gebhard et al, who harvested MCS using a plastic pipette of 2 mm tip diameter and centrifuged them to cell pellets (13), in the present investigation MCS were carefully harvested using a pasteur pipette and were not centrifuged. The use of a plastic pipette and centrifugation disrupted BHY MCS structure in the present investigation.…”
Section: Discussionmentioning
confidence: 80%